HUBUNGAN TINGKAT STRES DENGAN KEJADIAN TEKANAN DARAH IBU RUMAH TANGGA MASA PANDEMI COVID19 DI PKM BUA TAHUN 2021 - Ratnasari Iskandar Ratnasari Iskandar; Evawati Uly Evawati Uly; Hermawati Ikhsan Hermawati Ikhsan (Bina Generasi : Jurnal Kesehatan, 2022)
Background: Mothers are the group most likely to experience stress during the COVID-19 pandemic. In difficult times like this, the mother figure is forced to play multiple roles in the family. Stress can trigger changes in blood pressure, and body reactions that occur due to stress include shortness of breath, heart palpitations, and cold sweats. Objective: to determine the relationship between stress levels and blood pressure in housewives during the COVID-19 pandemic at the Bua Health Center in 2021. Methods: This study was analytic with a cross-sectional design. The population in this study were all housewives in the Bua Health Center area in the 2021 timeframe, sampling using purposive sampling, with as many as 80 respondents. Data retrieval tool for the variable stress level with Depression Anxiety Stress Scales (DASS21) and blood pressure measured by Spigmomanometer Manual. Data analysis using Frequency Distribution for respondents' stress levels. Result: The results showed that there was a relationship between stress levels and the incidence of hypertension in housewives during the COVID-19 pandemic (p = 0.000). Conclusion: There is a relationship between stress levels and blood pressure in housewives during a pandemic because stress levels are a condition where the body's condition is disturbed due to psychological pressure and stress can trigger hormones in the body that control a person's mind.